Determinants of Access and Farmers’ use of Information and Communication Technologies (1CTs) in Edo State, Nigeria - DN Okoedo-Okojie; FE Omoregbee (Journal of Applied Sciences and Environmental Management)
This study assessed determinants of farmers access and use of new ICTS in the study area. Data obtained from 270 respondents through multi-stage sampling technique were subjected to descriptive and logit regression analysis. The results show that GSM is the only new ICT farmers have access to (mean= 2.66) and use regularly (mean =3.44) while they have little or no access to and use either computer, E- mail or internet. This poor farmers access to and use of new ICTs can limit the extent of agricultural information they can receive. The probability of respondents having high access to new ICTS was significantly related to education (b = 0.784) and farming income, (b = 0.754). The study recommends organizing farmers into associations for training in the use of and collective acquisition of new ICTs. @JASEM